Human White and Brite Adipogenesis is Supported by MSCA1 and is Impaired by Immune Cells. (April 2015) - Estève, David; Boulet, Nathalie; Volat, Fanny; Zakaroff‐Girard, Alexia; Ledoux, Séverine; Coupaye, Muriel; Decaunes, Pauline; Belles, Chloé; Gaits‐Iacovoni, Frederique; Iacovoni, Jason S.; Rémaury, Anne; Castel, Benjamin; et al.
Abstract: Obesity‐associated inflammation contributes to the development of metabolic diseases. Although brite adipocytes have been shown to ameliorate metabolic parameters in rodents, their origin and differentiation remain to be characterized in humans. Native CD45−/CD34+/CD31− cells have been previously described as human adipocyte progenitors. Using two additional cell surface markers, MSCA1 (tissue nonspecific alkaline phosphatase) and CD271 (nerve growth factor receptor), we are able to partition the CD45−/CD34+/CD31− cell population into three subsets. We establish serum‐free culture conditions without cell expansion to promote either white/brite adipogenesis using rosiglitazone, or bone morphogenetic protein 7 (BMP7), or specifically brite adipogenesis using 3‐isobuthyl‐1‐methylxanthine. We demonstrate that adipogenesis leads to an increase of MSCA1 activity, expression of white/brite adipocyte‐related genes, and mitochondriogenesis. Using pharmacological inhibition and gene silencing approaches, we show that MSCA1 activity is required for triglyceride accumulation and for the expression of white/brite‐related genes in human cells. Moreover, native immunoselected MSCA1+ cells exhibit brite precursor characteristics and the highest adipogenic potential of the three progenitor subsets. Finally, we provided evidence that MSCA1+ white/brite precursors accumulate with obesity in subcutaneous adipose tissue (sAT), and that local BMP7 and inflammation regulate brite adipogenesis by modulating MSCA1 in human sAT. The accumulation of MSCA1+ white/brite precursors in sAT with obesity may reveal a blockade of their differentiation by immune cells, suggesting that local inflammation contributes to metabolic disorders through impairment of white/brite adipogenesis. Stem Cells 2015;33:1277–1291